2022
DOI: 10.1111/ddi.13634
|View full text |Cite
|
Sign up to set email alerts
|

Citizen science reveals meteorological determinants of frog calling at a continental scale

Abstract: Aim Here we investigate the strength of the relationships between meteorological factors and calling behaviour of 100 Australian frog species using continent‐wide citizen science data. First, we use this dataset to quantify the meteorological factors that best predict frog calling. Second, we investigate the strength of interactions among predictor variables. Third, we assess whether frog species cluster into distinct groups based on shared drivers of calling. Location Australia. Method To assess the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 92 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…In the present study, four citizen scientists found almost always 100% of the dogs detected by the most proficient investigator using GSV and this percentage decreased with fewer citizen scientists. The low detection of free-roaming dogs when fewer citizen scientists performed the search in the same community could be due to different causes, such as variability in performing the virtual tour, low visual acuity, differences in attention span, or lack of motivation to carry out a full search, this has been observed in other studies (41,42).…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, four citizen scientists found almost always 100% of the dogs detected by the most proficient investigator using GSV and this percentage decreased with fewer citizen scientists. The low detection of free-roaming dogs when fewer citizen scientists performed the search in the same community could be due to different causes, such as variability in performing the virtual tour, low visual acuity, differences in attention span, or lack of motivation to carry out a full search, this has been observed in other studies (41,42).…”
Section: Discussionmentioning
confidence: 65%
“…Although our surveys were widespread, they are unlikely to include all frog species present. Time of year and weather, in particular, influence frog calling activity (Thompson et al 2022), with some species only detectable under specific conditions (e.g. Litoria brevipalmata are rarely detected except after recent heavy rainfall).…”
Section: Discussionmentioning
confidence: 99%
“…Citizen science related to amphibian surveys is actively being conducted. Amphibians' distribution in specific regions is assessed through citizen science programs, and initiatives are undertaken to educate the public about the significance of amphibians [92][93][94]. Standardized procedures for amphibian conservation can be developed by holistically integrating these diverse methods.…”
Section: Methods For Studying Amphibians and Their Conservationmentioning
confidence: 99%